Innovative Educational Design for Oral Pathology: Current evidence on microlearning and a proposed instructional framework. - Carino, Silvia Norma; Aybar Odstrcil, Ana del Carmen (Spanish Journal of Medical Education, 2026)
Microlearning(ML) has become established as an innovative pedagogical strategy based on the presentation of brief, focused, and self-contained content, aimed at optimizing skills acquisition and reducing cognitive load. In the health sciences, its implementation has been enhanced by the use of digital tools (DGTs), especially in virtual, hybrid, and mobile learning contexts. The objectives of this study were to analyze the available evidence on the use of ML and DGTs in teaching oral pathology. A structured descriptive literature review was conducted, and based on the data obtained, an innovative instructional design for microlearning applied to the topic of malignant salivary gland neoplasms was proposed. A structured narrative literature review was conducted through searches in PubMed, Google Scholar, and SciELO, supported by the SciSpace tool. Studies published between 2010 and 2025 that evaluated educational interventions based on ML and/or DT in pathology or oral pathology were included. The results indicate that ML, implemented through microvideos, flashcards, infographics, and gamification strategies, is associated with improvements in student engagement, satisfaction, and academic performance, in several cases outperforming traditional teaching methods. In oral pathology, virtual microscopy (VM) stands out as a validated tool that enhances the understanding of histopathological patterns, clinicopathological integration, and diagnostic confidence. In conclusion, the integration of ML with DT, particularly VM, represents an effective pedagogical approach for teaching oral pathology. The proposed instructional design offers a relevant opportunity for educational innovation and highlights the need for longitudinal studies to assess its long-term impact and support its curricular integration.